Reimagining self-determination: relational, decolonial, and intersectional perspectives - Constantinou, CM; McConnell, F; Dirik, D; Regassa, A; Loong, S; Kuokkanen, R (Elsevier, 2024)
Self-determination language and practice are increasingly perplexing in the 21st century. Historically linked to decolonization processes and post-imperial transformations of the international system, self-determination has espoused both violent and non-violent resistance, and supported both existing and emergent sovereignty. With the Janus-faced relationship between self-determination and colonialism continuing to this day, the contemporary moment is an opportune time to take stock of self-determination. However, as conventional jurisprudence and international legalism framings have, in many ways, hampered its emancipatory potential, alternative ways of reimagining self-determination are needed. Bringing together scholars from the fields of political and development geography, indigenous studies, international relations, and sociology, this intervention demonstrates how articulations of self-determination in specific sites offer powerful critiques of the state system and the liberal world order and unsettle hegemonic forms of knowledge production. These articulations open up conceptual space to push self-determination beyond the realm of rights, allowing us to reimagine self-determination as a vision and practice, and to recover and reconceptualize the hopeful, emancipatory and aspirational politics that have always underpinned self-determination. This intervention seeks to re-envision self-determination from three novel and interlinked angles: decoloniality, intersectionality, and relationality. Drawing on a range of examples of contemporary and historical self-determination claims and contestations, each author focuses on one or more of these angles to examine the extent to which current practices of and visions for self-determination engender novel understandings of emancipation from ‘foreign’ domination and/or colonial systems of governance.